Strengthening Disaster Mitigation through Risk Communication in the Palm Oil Industry Occupational Safety and Health System: A Narrative Literature Review - Dewi Nuraliah; Rezki Rahmawati; Nurfadilah Nasiruddin; Moh. Iqbal Maulana; Dwi Rianisa Mausili (Kirana Publisher (KNPub), 2026)
The palm oil industry is a high-risk sector that faces various potential hazards and therefore requires a disaster mitigation strategy that is not only oriented to technical aspects, but also to risk communication. This study aims to analyze the role of risk communication in strengthening disaster mitigation through the Occupational Safety and Health system in the palm oil industry. The research uses a qualitative approach with a narrative literature review method. Data were obtained through literature searches on ScienceDirect, Google Scholar, SpringerLink, and DOAJ, then analyzed thematically through synthesis and interpretation processes. The results of the study show that risk communication plays a role in shaping risk perceptions, strengthening safety cultures, improving organizational preparedness, and supporting coordination in disaster mitigation. Risk communication also connects the technical aspects of the K3 system with the behavioral and governance aspects of the organization.